2003
DOI: 10.1126/science.1089268
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Coronary Function in Mice Deficient in α 1H T-type Ca 2+ Channels

Abstract: Calcium ion (Ca2+) influx through voltage-gated Ca2+ channels is important for the regulation of vascular tone. Activation of L-type Ca2+ channels initiates muscle contraction; however, the role of T-type Ca2+ channels (T-channels) is not clear. We show that mice deficient in the alpha1H T-type Ca2+ channel (alpha(1)3.2-null) have constitutively constricted coronary arterioles and focal myocardial fibrosis. Coronary arteries isolated from alpha(1)3.2-null arteries showed normal contractile responses, but reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
269
1
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 315 publications
(286 citation statements)
references
References 26 publications
15
269
1
1
Order By: Relevance
“…28 However, Cacna1h-deficient mice have no reported ptosis but rather cardiac fibrosis, which our two patients with CACNA1H homozygous truncation do not have. 29 Interestingly, heterozygous missense changes in CACNA1H have been associated with childhood epilepsy, but the two sisters we describe with a homozygous truncating mutation in this gene are completely normal neurologically except for ptosis. 30 This may suggest a different disease mechanism than we have previously shown for other genes in which biallelic loss of function results in distinct clinical phenotypes as compared with heterozygous mutations.…”
Section: Discussionmentioning
confidence: 68%
“…28 However, Cacna1h-deficient mice have no reported ptosis but rather cardiac fibrosis, which our two patients with CACNA1H homozygous truncation do not have. 29 Interestingly, heterozygous missense changes in CACNA1H have been associated with childhood epilepsy, but the two sisters we describe with a homozygous truncating mutation in this gene are completely normal neurologically except for ptosis. 30 This may suggest a different disease mechanism than we have previously shown for other genes in which biallelic loss of function results in distinct clinical phenotypes as compared with heterozygous mutations.…”
Section: Discussionmentioning
confidence: 68%
“…Specific ion channels mediate the rise in [Ca 2+ ] i within sperm, and many candidates for the principle Ca 2+ channel in sperm, including various voltagegated Ca 2+ channels, were proposed based primarily on studies using Ca 2+ imaging, immunolabeling, and patch-clamp experiments from sperm precursors [61][62][63]. However, genetic ablation studies suggested that these candidate proteins were not functionally necessary for male fertility or some compensatory mechanism for their loss may be present [64][65][66][67][68]. The molecular identity of the first sperm specific ion channel required for male fertility in mice was determined in 2001 with the cloning of CatSper1 [24].…”
Section: Calcium Channels and Hyperactivationmentioning
confidence: 99%
“…The Ca v 3.1-deficient mice have a blunted hypertensive response to infusion of L-NAME, which suggest that vascular-expressed Ca v 3.1 is important for bioavailability of NO and peripheral resistance (Svenningsen et al 2014). Ca v 3.2-deficient mice have abnormal coronary function with normal vasoconstrictor responses but reduced relaxation of coronary vascular smooth muscle after acetylcholine and nitroprusside (Chen et al 2003).…”
mentioning
confidence: 99%
“…cells; however, T-type calcium channels are also expressed in the cardiovascular system where they play a functional role in the regulation of both contraction and vasodilation (Hansen et al 2001, Chen et al 2003. The family of T-type channels is comprised of three isoforms: Ca v 3.1, Ca v 3.2 and Ca v 3.3, which have all been identified in the vasculature (Gustafsson et al 2001, Hansen et al 2001.…”
mentioning
confidence: 99%
See 1 more Smart Citation